Zn2GeO4@CeO2 Core@Shell Nanorods for Efficient Photocatalytic CO2 Reduction - Jin Sun; Yunxia Bai; Xilan Feng; Dapeng Liu; Yu Zhang (Molecules)
The enduring problem of CO2 emissions and their consequent influence on the earth’s atmosphere has captured the attention of researchers. Photocatalytic CO2 reduction holds great significance; however, it is constrained by the effect of carrier recombination. Simultaneously, the structural modification of heterojunction catalysts has emerged as a promising approach to boost the photocatalytic performance. Herein, Zn2GeO4@CeO2 core@shell nanorods were prepared by a simple self-assembly method for photocatalytic CO2 reduction. The thickness of the CeO2 shell can be regulated rapidly and conveniently. The photocatalytic results indicate that the structure regulation could affect the photocatalytic performance by controlling the amount of active sites and the shielding effect. X-ray photoelectron spectroscopy (XPS) and Mott–Schottky analyses reveal that Zn2GeO4 and CeO2 formed Type-I heterojunctions, which prolonged the lifetime of the photogenerated carriers. The CO2 adsorption and activation capacities of CeO2 also exert a beneficial influence on the progress of CO2 photoreduction, thus enabling efficient photocatalytic CO2 reduction. Moreover, the in situ FT-IR spectra show that Zn2GeO4@CeO2 suppresses the formation of byproduct intermediates and shows higher CO selectivity. The best sample of Zn2GeO4@0.07CeO2 can exhibit a CO yield of as high as 1190.9 μmol g−1 h−1.